2013
DOI: 10.1037/a0032181
|View full text |Cite
|
Sign up to set email alerts
|

Extinction makes conditioning time-dependent.

Abstract: Two experiments explored whether forgetting of an association depended on previous extinction of a different association in rats. Experiment 1 found that when rats were conditioned and extinguished with flavor X, a subsequently acquired conditioned aversion to flavor Y was reduced by a 19-day retention interval, something that did not occur when X and the US were initially presented unpaired. Experiment 2 found that when rats received training and extinction in one of two tasks (conditioned aversion to sucrose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 42 publications
2
12
0
Order By: Relevance
“…The findings previously mentioned are consistent with the ATCP because they suggest that after extinction of Flavor X rats attended to the context producing a contextual specificity in the learning of Y. Similar results were obtained using temporal contexts with rats (Bernal-Gamboa, Callejas-Aguilera, Nieto & Rosas, 2013) and fictional contexts with human participants ; see also, Nelson & Callejas-Aguilera, 2007;Nelson, Lamoureux, & Leon, 2013).…”
Section: Attentional Theory Of Context Processingsupporting
confidence: 82%
“…The findings previously mentioned are consistent with the ATCP because they suggest that after extinction of Flavor X rats attended to the context producing a contextual specificity in the learning of Y. Similar results were obtained using temporal contexts with rats (Bernal-Gamboa, Callejas-Aguilera, Nieto & Rosas, 2013) and fictional contexts with human participants ; see also, Nelson & Callejas-Aguilera, 2007;Nelson, Lamoureux, & Leon, 2013).…”
Section: Attentional Theory Of Context Processingsupporting
confidence: 82%
“…In rats, the EMACS effect has also been found in conditioned taste aversion (Bernal-Gamboa et al, 2015;Bernal-Gamboa et al, 2018;. Moreover, the EMACS effect has been found to persist across different tasks in both human and nonhuman animals (Bernal-Gamboa et al, 2013;Bernal-Gamboa et al, 2014;; but see Nelson & Lamoureux, 2015;Nelson, Lombas, & León, 2011 for results that qualify these findings).…”
mentioning
confidence: 88%
“…52 ). More recently, Bernal-Gamboa, Callejas-Aguilera, Nieto, and Rosas 54 found that CS-US and response-outcome associations are more “forgettable” over time if there has been previous exposure to extinction of a different association, even within a different task. That result suggests that changes in the temporal context may play a role that is similar to the one played by changes in physical contexts.…”
Section: Conditions That Allow Contextual Controlmentioning
confidence: 99%